the racial and cultural mixing in Peru - Amat Olazával, Hernán (2013)
The phenomenon is quintessential American racial miscegenation, generated by the Spanish invasion and, in addition, the distinctive cultural phenomenon of the American people, becomes a syncretism or fusion of its life forms adapted into a new pattern, the cultural mix and religious. This article seeks to explain how they lived oppressed Andean women and children charged with first mestizos almost all bastards, with the offspring born in these lands whites relations «conquerors» with young women converted to mistresses or concubines. It also analyzes the life of the first mestizo born in the fateful years of the «civil wars» and early days of the Colony: Francisca Pizarro Yupanqui, Maria Yupanqui Betanzos, Beatriz Coya Loyola famous mestizo Inca Garcilaso de la Vega, Carlos Inca, Blas Valera, Tupac Amaru, Juan Avendaño Azarpay, among others.